Constructing the subject, deconstructing the text: the feminist other in Achebe's Anthills of the Savannah - Alkali, Muhammad; Talif, Rosli; Mohd Jan, Jariah (Universiti Putra Malaysia Press, 2015)
The paper begins with a reminder of early criticism on traditional feminism and then traces the beginnings of occasional opposition leading to provocative positions through representative works and criticisms of some writers and critics. The paper, therefore, identifies a trilogy and moves to uphold the last of the trilogy which might startle the revolutionary feminist because it is more accommodating in its gender approach than the revolutionist would aspire to in dismantling the hegemonic phallus. It submits that there is certainly revelation in deconstructing, transforming, re-inscribing and negotiating "male patriarchy" as this leads to a conversation that empowers its readers to soft-pedal on both anti-masculinity and anti-femininity, an argument towards policy reform on gender. In doing this, it uses nego-feminist theory to locate and critique Chinua Achebe's sudden change from anti-thesis of feminism to gender justice through his last novel, Anthills of the Savannah. However, it hypothetically praises Achebe's stand for being feminist and then questions it for being improperly feminist.